Extraction of gold from agricultural drones' waste components through Thiourea leaching - Stefany Vier Steffen; Hugo Marcelo Veit (REM: International Engineering Journal, 2025)
Abstract The global commercial drone market is experiencing rapid growth, particularly in precision agriculture applications such as crop spraying. This market is projected to expand at an 8.3% compound annual growth rate (CAGR), contributing to an overall drone market value of approximately $55.8 billion by 2030. Agricultural drones are made of various materials including electronic waste components such as circuit boards, connectors, and pins, containing significant amounts of gold. While gold cyanidation is the primary method for gold extraction, there is a growing interest in more environmentally friendly alternatives. This study focuses on extracting gold from pins using thiourea-based leaching with temperature variation and ultrasound agitation, comparing it to conventional cyanide processes. The process begins with the X-ray fluorescence analysis of drone components to detect gold. The gold concentration in pins is measured through aqua regia digestion (1:25 ratio, 70°C, 2 h). Cyanide leaching is conducted at 25°C for 2 h at pH 14, with a 1:25 mass ratio, while Thiourea leaching is performed at a 1:10 ratio for 2 h and pH 1, under different conditions: varying temperature and ultrasonic agitation. Cyanide digestion shows about 83 ppm of gold, setting a standard recovery benchmark of 100%. In contrast, aqua regia yields 66.8%. The thiourea leaching's efficiency, influenced by temperature and agitation, sees its highest gold recovery at 43.19% of the cyanide standard, with ultrasonic agitation, although overall performance is below cyanide yields. Further research is needed to enhance gold recovery through thiourea based leaching, focusing on optimizing the temperature parameters and leaching conditions.